2022
DOI: 10.1371/journal.pone.0274119
|View full text |Cite
|
Sign up to set email alerts
|

A gender-based investigation into the required English language policies in Saudi higher education institutions

Abstract: The Saudi Arabian higher education system is yet to address specific issues concerning language planning and policy. Policies concerning English language use in Saudi academia remain ungoverned, thus leading to implicit personal policies (i.e., self-directed policies). Such freedom in language use may generate concerns among stakeholders, especially if differences emerge between men and women in the same workplace. Current literature does not offer insights into how English is used by each gender in academic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
1
3
2
Order By: Relevance
“…The discrepancy observed between the findings of our study and those of previous research, such as the studies by Alnasser (2022) and Liu et al (2022), potentially arises from divergent educational, and methodological factors. The studies by Alnasser and Liu et al were conducted in Saudi Arabia, where gender norms and expectations in educational settings may influence student performance differently compared to the context of our study.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The discrepancy observed between the findings of our study and those of previous research, such as the studies by Alnasser (2022) and Liu et al (2022), potentially arises from divergent educational, and methodological factors. The studies by Alnasser and Liu et al were conducted in Saudi Arabia, where gender norms and expectations in educational settings may influence student performance differently compared to the context of our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with the primary objective, our study's outcomes indicated that there is no significant difference between male and female students in comprehensive tests. This observation notably diverges from other research, such as the study by Alnasser (2022) in Saudi Arabia, which saw female students excelling beyond male counterparts in areas like mathematics and science. Moreover, an analysis of combined national and international assessment data from the same region reinforced these findings, showing girls to surpass boys across similar academic disciplines and educational levels (Liu et al, 2022).…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…The study indicates that incorporating cultural heritage courses into Saudi Arabian college curriculums is crucial for the Saudi Education sector (Alhefnawi et al, 2023). Saudi Arabia's higher education system lacks language planning and policy, with unrestricted English language use in academics, potentially raising concerns about gender disparities in professional environments (Alnasser, 2022). Government of Saudia Arabia are progressively exploring the use of AI in several public sector domains, such as military operations, surveillance, healthcare services, medical research, transportation, education, and emergency response (Alshahrani et al, 2022).…”
Section: Public Perception and Participation In Government Initiativesmentioning
confidence: 99%